Abundance of small indigenous species of fish (SIS) at Trishal, Mymensingh (Bangladesh Journal of Zoology, 2010)
An investigation was conducted to find the richness and diversity of small indigenous species (SIS) of fish at Trishal upazila in Mymensingh district of Bangladesh. Sampling was carried out frequently over a year in selected landing stations, fish markets and catch points. A total of 54 SIS belonging to 41 genera, 23 families and 10 orders was recorded. The most dominant family was Cyprinidae comprising 18 species under the order Cypriniformes. Puntius was the largest genus including six species. The most abundant SIS was Tengra (Mystus sp.) during the investigation period, whereas the least abundant SIS was Bacha (Eutripiichthyes vacha). Seasonal variations were observed in the abundance of different SIS.Bangladesh J. Zool. 38(1): 105-112, 2010